(untitled) (Al-Academy, 2022)
The rapid breakthrough achieved by technological progress in the field of designing and implementing women’s fashion has resulted in the emergence of the need for quality control and control to improve the completed visual image of fashion as an aesthetic and functional product and not clothed in its abstract qualities.The quality in women’s fashion and the importance of showing the design and conveying the design message to the recipient depends on the level of its implementation, starting from the selection of textile fibers and determining their appropriate characteristics for the functional purpose and design prepared by the designer and ending with the final operations of the costume. This calls for spreading awareness and culture of the concept of quality among all recipients, dealers and specialists in women’s fashion to improve the mental image of fashion as an aesthetic and functional achievement.Hence, the research is directed to study the topic (the importance of quality standards in the designs of fabrics and women’s fashion), which deals with the research problem based on the imposition of the following question:What are the quality standards and their importance in the designs of fabrics and women’s fashion?The aim of the research was to "know about the importance of quality standards and their applications within the production stages of designing fabrics and designing women’s fashion."As for the limits of the research, it was limited to the adoption of women’s fashion completed within the time period (2022), which was obtained from online shopping outlets.(https://miswag.net/dept/fashion - https://www.lcwaikiki.iq/fashio), according to selection considerations and within the limits of the research and its procedures. The theoretical framework was dealt with, including two sections, which were distributed as follows:The first topic: quality standards.The second topic is the indicators of judging the quality of women’s fashion.The research procedures were determined by taking the descriptive approach to analyze the (4) samples, and their selection was according to what serves the research objectives. The researcher reached the most important conclusions as follows:1- The relationship between the designer and the implementing agency for women’s fashion is a consensual relationship, through which it is imperative that the designer not be exaggerated in the design units, taking into account clarity in its elements, which leads to reducing the chance of operational errors of the outfit and showing the design within its aesthetic and technical characteristics.2- The models showed an agreement on the necessity of quality control for all stages of implementation, starting from the quality of the fibers and ending with the complementary works of the uniform. And poor quality at any stage of implementation necessarily leads to women’s fashion losing its formal and aesthetic appearance associated with the design prepared for it.ConclusionsIn light of the results of the sample analysis, the researcher concluded the following:1- The relationship between the designer and the executing agency for women’s fashion is a consensual relationship, through which it is imperative to apply the standard of codification by the designer in the design units and not to exaggerate them, taking into account clarity in its elements, which leads to reducing the chance of operational errors of the dress and showing the design within its aesthetic and technical characteristics.2- The attention of specialists in the women’s clothing industry in the type and quality of the fabric and the renewal of its prior suitability with the prepared design in terms of the degree of softness, wrinkle ability, texture, dimensional stability and resistance to damage in proportion to the time factor of use.3- Dyeing, printing and its quality are among the most important executive stages for cloth and clothing, through which it is determined to show the design prepared by the designer and the technical idea inherent in the design.4- The quality of the procedural processes for implementing and sewing the dress determines the acceptability of the dress by the beneficiary first. Then interact with the design prepared for it to reach the stage of acceptance and approval.5- The models showed an agreement on the necessity of quality control for all stages of implementation, starting from the quality of the fibers and ending with the complementary works of the uniform. And poor quality at any stage necessarily leads to women’s fashion losing its formal and aesthetic appearance associated with the design prepared for it.6- Spreading awareness and culture of the importance of quality and adherence to its standards among workers and specialists in the women’s clothing industry to improve the completed visual image of fashion as an aesthetic and functional product and not clothed in its abstract qualities.